THE TRANSFORMATION OF THE MUAMALAH FIQH AKAD AT SAGA ABEPURA-PAPUA MALL DURING THE COVID 19 PANDEMIC - Amirullah, Amirullah; Pasinringi, Andi Achruh AB.; Sahib, Rahmawansyah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2020)
This article comes with a new perspective to understand the community transactions dynamics at the Saga Abepura Mall, Papua (MSA). The Covid-19 period challenges MSA managers in carrying out contract transformation. This article takes a close look at the changes in the muamalah fiqh agreement from offline to online, significantly transforming contract transactions at MSA during the Covid-19 pandemic. Two points are studied. First, muamalah fiqh transactions concerning contract transformation. Second, an analysis of contract changes. The focus of this article is on changing the old contract to the new contract. This article considers that a new contract is allowed in muamalah jurisprudence as long as there is no opposition with the Al-Qur'an and Al-Hadith. This article seeks answers to questions using observational data and interviews. The interview involved seven informants. They are four MSA employees and three customers. Transactions in a new contract do not mean replacing the old contract law. Creating a muamalah contract transformation does not have to eliminate other covenants. The existence of transforming an online buying and selling contract gave birth to a new form of contract at MSA, namely the order contract. First, the salam contract is the contract when the goods are paid for in advance, while the isthisnah contract was the contract when the order is paid when the good is in hand. Thus, all agents, MSA managers, customers, and employees should pay attention to contract transformation.تأتي هذه المقالة مع منظور جديد لفهم ديناميكيات المجتمع في الصفقة في مولSaga Abepura-Papua (MSA) ، تمثل فترة كوفيد-19 تحديات لمديري المول في تنفيذ تغيير العقد. تنظر هذه المقالة نظرة فاحصة على التغيير في عقد فقه المعاملة من العقد المباشر وغير المباشر عبر الإنترنيت في المول فترة كوفيد-19. هناك شيئان مهمان يتم دراستهما الأول صفقة فقه المعاملة المتعلقة بتغيير العقد والثاني تحليل تغيير العقد. التركيز في هذه المقالة هو تغيير العقد القديم إلى العقد الجديد. تعتبر هذه المقالة أن العقد الجديد مسموح به في فقه المعاملة بشرط عدم وجود دليل في القرآن الكريم والسنة النبوية على تحريمه. تسعى هذه المقالة للحصول على إجابات للأسئلة باستخدام بيانات المراقبة والمقابلات. تشمل المقابلة سبعة مخبرين، أربعة موظفي المول وثلاثة عملاء، الصفقة في العقد الجديد لا تعني محو حكم العقد القديم، التغيير في فقه المعاملة لا يلزم إلغاء العقود الأخرى، وقوع التغيير في عقد المعاملة عبر الإنترنيت يؤدي إلى ظهور شكل جديد من العقود في المول وهو عقد الطلب. الأول عقد السلم هو دفع قيمة البضائع المطلوبة مقدمًا، وأما عقد الاستصناع هو دفع ثمن البضائع المطلوبة في النهاية عند استلام الطلب. وهكذا كل الأطراف من مديري المول والعملاء والموظفون يهتمون بتغيير العقد.Artikel ini hadir dengan perspektif baru untuk memahami dinamika masyarakat dalam bertransaksi di Mall Saga Abepura-Papua (MSA). Masa Covid-19 memberikan tantangan terhadap pengelola MSA dalam melakukan transfomasi akad.Artikel ini melihat dari dekat kaitan perubahan akad fikih muamalah dari offline ke online khususnya bagaimana transformasi akad bertransaksi di MSA pada masa pandemi covid-19. Ada dua hal penting yang dikaji. Pertama, transaksi fikih muamalah tentang transformasi akad. Kedua, analisis perubahan akad. Fokus dalam artikel ini adalah perubahan akad lama kepada akad baru. Artikel ini memandang bahwa akad baru dibolehkan dalam fikih muamalah asalkan tidak ada dalil Alqur’an dan Alhadis yang melarangnya. Artikel ini mencari jawaban atas pertanyaan-pertanyaan dengan menggunakan data observasi dan wawancara. Wawancara melibatkan tujuh informan. Empat orang karyawan MSA dan tiga orang konsumen. Transaksi dalam akad baru bukan berarti manghapus hukum akad yang telah lama. Menciptakan transformasi akad muamalah tidak harus menghilangkan akad-akad yang lainnya. Adanya transformasi akad jual beli online melahirkan bentuk akad baru di MSA, yakni akad pesanan. Pertama akad salam adalah pembayaran barang pesanan yang di bayar diawal, sedangkan akad isthisnah adalah pembayaran barang pesanan yang dilakukan diakhir yakni ketika pesanan sudah di tangan. Dengan demikian semua pihak, pengelola MSA, pelanggan dan karyawan memperhatikan transformasi akad.